A Public Financial Management Framework for Resources-Producing Countries - Helis, Jean-Luc (IMF Working Papers; Working Paper, 2010)
This working paper overviews the challenges posed by resource revenues management and the policy prescriptions to meet them, and focuses on the Public Financial Management (PFM) framework and reforms that resource-producing countries should adopt. The paper outlines a PFM framework and reform path that take into account the institutional diversity of resource-producing countries. In the short term, the proposed reforms highlights the tools that could be implemented even where the PFM system is rather basic, while over the medium and long term they aim at converging with best international PFM practices.